Obesity and Metabolic Syndrome in Adolescents: A Growing Clinical Challenge - SHUJA, NAVEED (Pakistan Journal of Medical & Health Sciences, 2026)
Nowadays, adolescent obesity has emerged as one of the major clinical and public health problems¹. Obesity, once viewed primarily as a cosmetic or lifestyle issue, is now understood as a complex medical condition linked to insulin resistance, hypertension, dyslipidaemia, fatty liver disease, psychological stress and early cardiovascular risk². In 2022, the World Health Organization (WHO) reported that over 390 million children and adolescents aged 5-19 years were overweight, with overweight prevalence rising from 8% in 1990 to 20% in 2022³. This quick increase reflects that obesity is no longer confined to adulthood but is starting to take root in childhood and adolescence⁴. Metabolic syndrome in adolescents represents a clustering of cardiometabolic abnormalities, including central obesity, raised blood pressure, impaired glucose regulation, high triglycerides, and low high-density lipoprotein cholesterol⁵. The significance of its importance is that these abnormalities are frequently subclinical in the early years and slowly contribute to the increased risk of type 2 diabetes mellitus, cardiovascular disease, chronic kidney disease, and non-alcoholic fatty liver disease (NAFLD)⁶. The risk of metabolic syndrome is significantly higher for adolescents with overweight and obesity than for normal-weight adolescents, and research indicates that the risk for overweight adolescents is several-fold higher⁷. Changing social and environmental patterns compound the clinical challenge. Increased consumption of calorie-dense processed foods, sugar-sweetened beverages, sedentary screen-based behavior, reduced outdoor activity, poor sleep, academic stress, and family history of metabolic disease all contribute to the problem⁹. However, obesity is also commonly overlooked in many communities, with overweight in teens sometimes being confused as a natural part of growth or “a healthy look.” This late recognition permits the metabolic complications to develop in a silent way¹⁰. The consequences of adolescent obesity extend beyond physical health¹¹. Affected adolescents often have low self-esteem, are anxious, depressed, socially isolated, bullied and have decreased involvement in school and sports activities¹². These psychological effects can even exacerbate eating habits and physical inactivity, which can further perpetuate a negative cycle of effects.¹³ Thus, it is important that management should not be limited to weight loss, but that the emotional health, the family support and the sustainable behavioral change as well should be taken into account¹⁴. Early screening is of critical importance¹⁵. Body mass index percentile, waist circumference, blood pressure, fasting glucose, lipid profile, liver enzymes, and family history should be assessed in adolescents with obesity or rapid weight gain¹⁶. Additional work-up for insulin resistance, fatty liver disease, sleep apnea, and endocrine diseases may be warranted in high-risk patients¹. The goal should be to achieve early detection, before irreversible cardiometabolic damage occurs,². Prevention is the best approach³. It is important for schools, families, health care providers and policy makers to collaborate to encourage healthy eating, physical activity, limiting screen time, good sleep hygiene, and early counseling⁴. Treatment should be tailored to the person and not stigmatizing. Adolescents should not be blamed for obesity; instead, they should be supported within their family and social environment⁶. Lifestyle modification remains the foundation of treatment, but multidisciplinary care involving pediatricians, nutritionists, psychologists, endocrinologists, and physical activity specialists is often needed for sustained improvement⁷. In conclusion, obesity and metabolic syndrome in adolescents represent a growing clinical challenge with lifelong consequences⁸. The adolescent period provides a critical window for prevention, early diagnosis, and intervention⁹. Taking action early can minimise the risk of diabetes, cardiovascular disease and other metabolic problems in adulthood¹⁰. Addressing this problem requires not only medical treatment but also a broader public health approach that reshapes diet, activity, education, and community awareness¹¹.